Integrasi Media Smartboard dalam Model Direct Instruction untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Laju Reaksi - Feby Stefania Baan Tasik; Army Auliah; Sugiarti Sugiarti (Entalpi Pendidikan Kimia, 2026)
The integration of technology in chemistry learning is increasingly essential to overcome the abstractness of chemical concepts. This study aims to examine the effect of smartboard media integration within the Direct Instruction model on students' learning outcomes in reaction rate material. A pre-experimental approach with a One Group Pretest-Posttest Design was used, involving 43 students of class X.E at SMK SMAK Makassar selected through purposive sampling. Data were collected through pretest and posttest instruments, then analyzed using the Wilcoxon Signed Rank Test, N-Gain, and Cohen's d effect size. The results showed an increase in the average score from 49.30 in the pretest to 61.16 in the posttest. The Wilcoxon Signed Rank Test confirmed a significant difference (Asymp. Sig. = 0.000 < 0.05). Although the N-Gain value of 0.21 fell in the low category partly attributed to the ceiling effect for high-pretest students and the inherent conceptual complexity of reaction rate the Cohen's d value of 0.73 indicated a medium practical effect, comparable to other innovative chemistry teaching strategies. The synergy between smartboard's dynamic visualizations and the structured, step-by-step delivery of Direct Instruction effectively facilitated students' understanding of abstract submicroscopic concepts such as collision theory and activation energy. These findings suggest that smartboard-integrated Direct Instruction is a pedagogically promising approach for chemistry classrooms equipped with interactive technology, while differentiated feedback strategies are recommended to further optimize individual learning gains.